A qualitative case study of LifeGuide: Users' experiences of software for developing Internet-based behaviour change interventions. (March 2013) - Williams, Sarah; Yardley, Lucy; Wills, Gary B
Previously, behavioural scientists seeking to create Internet-based behaviour change interventions have had to rely on computer scientists to actually develop and modify web interventions. The LifeGuide software was designed to enable behavioural researchers to develop and adapt Internet-based behavioural interventions themselves. This article reports a qualitative case study of users' experiences and perceptions of the LifeGuide software. The aim was to explore users' experiences and their perceptions of the benefits and limitations of this approach to intervention development. Twenty LifeGuide users took part in semi-structured interviews and one provided feedback via email. Thematic analysis identified three overarching themes: 'Recognising LifeGuide's potential', 'I'm not a programmer' and 'Knowledge sharing – the future of LifeGuide'. Users valued LifeGuide's potential to allow them to flexibly develop and modify interventions at little cost. However, users noted that their lack of programming experience meant that they needed to learn new skills for using the software, and they varied in the extent to which they felt able to develop interventions without any input from programmers. Respondents saw the potential of using the LifeGuide Community Website to share technical support and examples of intervention components to support their use of LifeGuide.